The rise and fall of liberal adult education: CSLEA at mid-century - Ronald Podeschi (Adult Education Research Conference, 1994)
Drawing from archival sources concerning the Center for the Study of Liberal Education for Adults (CSLEA), and from secondary literature about the 1950s and 1960s, an analysis is made of the contextual forces that influenced the growth and the demise of CSLEA. This research was made possible in part by support from the Syracuse University Kellogg Project.